Carcass quantitative traits of intact and castrated Hereford males, slaughtered at fourteen months - Restle, João; Vaz, Fabiano Nunes (Pesquisa Agropecuaria Brasileira, 1997)
Quantitative carcass characteristics of Hereford males, young bulls and steers, feedlot finished and slaughtered at 14 months of age were studied. No significant difference for live weight and dressing percentage were observed. However, the carcass weight was higher on young bulls, being the hot and cold carcass weight, respectively, 214 kg and 207 kg on young bulls and 195 kg and 190 kg, on steers. No significant difference in carcass length, arm length, arm perimeter, cushion thickness and Longissimus area were observed. Young bulls showed carcass with better conformation and higher forequarter percentage, while the steers showed higher percentage of pistol cut. Fat thickness did not differ significantly between the two carcass groups, being 4.95 mm and 5.98 mm on young bulls and steers, respectively.